Effect of Acetabular Position on Polyethylene Liner Wear Measured Using Simultaneous Biplanar Acquisition - Goyal, Prateek; Howard, James L.; Yuan, Xunhua; Teeter, Matthew G.; Lanting, Brent A. (The Journal of arthroplasty, 2017)
Studies that have previously examined the relationship between acetabular component inclination angle and polyethylene wear have shown increased wear of conventional polyethylene with high inclination angles. To date, there are no long-term in vivo studies examining the correlation between cup position and polyethylene wear with highly crosslinked polyethylene. An institutional arthroplasty database was used to identify patients who had metal-on-highly crosslinked polyethylene primary total hip arthroplasty using the same component design with a minimum follow-up of 10 years. A modified radiostereometric analysis examination setup was utilized, recreating standard anteroposterior and cross-table lateral examinations in a single stereo radiostereometric analysis acquisition. The same radiographs were used to measure inclination angle and anteversion. A total of 43 hips were included for analysis in this study. Average follow-up was 12.3 ± 1.2 years. The average linear wear rate was calculated to be 0.066 ± 0.066 mm/y. Inclination angle was not correlated with polyethylene wear rate (P = .82). Anteversion was also not correlated with polyethylene wear rate (P = .11). At long-term follow-up of >10 years, highly crosslinked polyethylene has a very low wear rate. This excellent tribology is independent of acetabular position. The low wear rate highlights the excellent results of metal on highly crosslinked polyethylene, and supports its use in total hip arthroplasty.